Validation of the graded prognostic assessment for lung cancer with brain metastases using molecular markers (lung-molGPA) - Nieder, Carsten (Radiat Oncol, 2017)
BACKGROUND: Many patients with brain metastases from non-small cell lung cancer have limited survival, while others survive for several years, depending on patterns of spread, EGFR and ALK alterations, among others. The purpose of this study was to validate a new prognostic model (Lung-molGPA) originally derived from a North American database. PATIENTS AND METHODS: This retrospective study included 269 German and Norwegian patients treated with individualized approaches, always including brain radiotherapy. Information about age, extracranial spread, number of brain metastases, performance status, histology, EGFR and ALK alterations was collected. The Lung-molGPA score was calculated as described by Sperduto et al. RESULTS: Median survival was 5.4 months. The score predicted survival in patients with adenocarcinoma histology and those with other types. For example, median survival was 3.0, 6.2, 14.7 and 25.0 months in the 4 different prognostic strata for adenocarcinoma. The corresponding figures were 2.4, 5.5 and 12.5 months in the 3 different prognostic strata for non-adenocarcinoma. CONCLUSIONS: These results confirm the validity of the Lung-molGPA in an independent dataset from a different geographical region. However, median survival was shorter in 6 of 7 prognostic strata. Potential explanations include lead time bias and differences in treatment selection, both brain metastases-directed and systemically.